Challenges of Biological Aging. - Masoro, Edward J. (Springer Pub. Co., 1999)
This volume provides the non-biologist an overview of what is known about the physiological bases of aging. The author examines the many basic theories and emerging hypotheses underlying the molecular, cellular, and systemic processes involved in senescence. He addresses the normal physiological changes that characterize the aging phenotype, and also considers the role of many age-associated diseases in growing older. Masoro synthesizes a much-needed "unified theory" of biological aging to which explains how and why the body grows into the condition we call "old." This text.